1987
DOI: 10.1149/1.2100400
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Ion Etching in  SF 6 Gas Mixtures

Abstract: Reactive ion etching of crystalline silicon, polysilicon, SIO2, and Si3N4 has been studied in a parallel plate electrode configuration, with and without magnetic confinement, in SF6 gas diluted with varying proportions of 02, N2, H2, and Ar. In order to investigate the contamination from the RF cathode, RIE studies were done with RF cathode covered with aluminum disk as well as with 0.5 cm thick circular quartz plate. The RF frequency used is 13.56 MHz and RF power density varied from 0.1 to 0.4 Wcm -2. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…The latter compound undergoes hydrolysis to form SO 2 F 2 , which is even more stable. Because hydrolysis requires significant water concentration, a downward diffusion of SF 4 O and/or SO 2 F 2 from the stratosphere into more humid air should be observable. Finally, SO 2 F 2 hydrolyzes very slowly (yields sulfuric acid and HF) which makes it suitable as a tracer for SF 6 or SF 5 CF 3 degradation in the atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The latter compound undergoes hydrolysis to form SO 2 F 2 , which is even more stable. Because hydrolysis requires significant water concentration, a downward diffusion of SF 4 O and/or SO 2 F 2 from the stratosphere into more humid air should be observable. Finally, SO 2 F 2 hydrolyzes very slowly (yields sulfuric acid and HF) which makes it suitable as a tracer for SF 6 or SF 5 CF 3 degradation in the atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…[2] Because SF 6 is an excellent source of fluorine atoms upon strong excitation and contains no carbon, it leaves no carbonaceous deposits in the plasma etching process. [3][4][5] An attractive feature of SF 6 is its nonflammability and chemical inertness. Surprisingly, the environmental concerns of the long-term usage of SF 6 have become an issue only recently as a result of its increasing abundance in the atmosphere.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Even though this method is a good option for Si isotropic etching, the XeF2 is expensive and rare [4]. Reactive-Ion Etching (RIE) based on the physical/chemical process using SF6 plasma is also an effective method for the isotropic etching of silicon due to a high density of radicals (SF5 * and F*) responsible for the Si lateral etching [5,6]. However, preliminary tests have shown that SF6 plasma causes damage to Au thin films as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%